(untitled) (Research, Society and Development, 2023)
The search for healthy and practical foods drives the creation of new products by the food industries, which is influenced by consumer behavior (dictated by economic, cultural and hedonic factors). The ice cream sector is a market to be explored with regard to the use of exotic ingredients that add nutritional value to the product. The objective of this work was to evaluate the opinion and behavior of consumers in relation to tamarillo ice cream with the addition of yam flour as a step in the development of a new product. A market survey was carried out using a questionnaire with 140 respondents. Respondents consider ice cream as a dessert (a factor related to how it is consumed), which is consumed due to its sensory and nutritional characteristics. In relation to the proposed new product, the use of individual, plastic and handcrafted packaging were some of the characteristics pointed out by the interviewees. It is concluded that the participants have a concern with healthiness since a concern is observed both with the information on the label and with the ingredients present in the product. The data indicate that the participants showed interest in the new product, demonstrating that it has a consumer market that can be a way of valuing regional products such as tamarillo.